2020
DOI: 10.1021/acsapm.9b01149
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Interaction Regulation by Protein Corona Control of Molecularly Imprinted Polymer Nanogels Using Intrinsic Proteins

Abstract: Nanomaterials have a great potential for use in various biorelated applications such as drug delivery systems and in vivo imaging; understanding nanoparticle–cell interactions is an important requisite for these applications. Herein, the nanoparticle–cell interactions, including the cellular uptake mechanism, were investigated in detail using polymer nanogels possessing molecular recognition ability (molecularly imprinted polymer nanogels: MIP-NGs) capable of protein corona regulation via albumin recognition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…One of such limitations is the formation of a protein corona that sterically blocks the active binding sites of target molecules and activates the complement. [76][77][78] However, it is important to note that this problem is intrinsic to nanoparticle-based systems in general. Successful solving this problem is a matter of future research.…”
Section: Discussionmentioning
confidence: 99%
“…One of such limitations is the formation of a protein corona that sterically blocks the active binding sites of target molecules and activates the complement. [76][77][78] However, it is important to note that this problem is intrinsic to nanoparticle-based systems in general. Successful solving this problem is a matter of future research.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of opsonin proteins in the corona, such as IgG, will cause the phagocytosis of the MIPs by “blood-cleaning” macrophages, preventing them from reaching their targets. Coating the MIP-NPs with a hydrophilic polymer layer of PEG , or albumin , could be useful to avoid clearance. Indeed, recent studies by Takeuchi’s group , have shown that a preformed corona of serum albumin on MIP nanogels, acquired in vivo thanks to the particles being surface-imprinted with albumin, can avoid immune responses because no inflammatory reactions in macrophages were observed, as measured by cytokine secretion.…”
Section: In Vitro and In Vivo Imaging With Mipsmentioning
confidence: 99%
“…Data also report favorable accumulation of the MIP-NPs at the tumor site and pharmacokinetics, despite the fact that most of them were bare and yet they did not seem to be affected by the opsonization phenomenon. In the bloodstream, the protein corona ,, changes the size and charge of the MIP-NPs, yet their hydrodynamic diameter in blood and their zeta potential in buffer or other fluids are rarely or not at all measured (Supporting Information, Table S1). Moreover, no studies have shown total reduction of tumors and full survival of the mice after treatment.…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…Parameters important to consider, specific for in vivo imaging, are biocompatibility, fluorescence (fluorophores need to emit in the near-infrared range to penetrate in deep tissues) and opsonisation, which needs to be avoided because immunoglobulins, in the blood stream, recognize nanoparticles as stranger elements and the immune system promotes their elimination. This last problem was solved by resorting to the coating of the MIP nanoparticles with a hydrophilic polymer layer of PEG [ 160 ] or albumin [ 161 ].…”
Section: Molecularly Imprinted Polymers (Mips)mentioning
confidence: 99%